Critical Photoperiod Measurement of Soybean Genotypes in Different Maturity Groups. Issue 5 (25th July 2019) - Yang, Wenying; Wu, Tingting; Zhang, Xinyue; Song, Wenwen; Xu, Cailong; Sun, Shi; Hou, Wensheng; Jiang, Bingjun; Han, Tianfu; Wu, Cunxiang
Abstract : Soybean [ Glycine max (L.) Merr.] is a photoperiod‐sensitive crop, and the photoperiod response determines the ecological adaptability of soybean genotypes. Critical photoperiod is the dividing daylength between photoperiod sensitivity and photoperiod insensitivity phases and is one of the most important indicators of photoperiod sensitivity. However, the appropriate experimental treatment and calculation method for quantifying the critical photoperiod are poorly documented. To characterize the photoperiod response of genotypes, 72 soybean genotypes belonging to 14 different maturity groups (MG 0000–MG X) were included, and five photoperiod treatments of 12‐, 14‐, 16‐, 18‐, and 20‐h daylength were conducted in the consecutive 3 yr from 2015 to 2017. The piecewise linear regression model based on the median function was used to determine the critical photoperiod. The results showed that the photoperiodic responses of soybean genotypes were significantly different among various MGs. The critical photoperiod of MG 0000 was 16.4 h d −1, whereas those of MG 000 to MG I, MG II to MG III, MG IV, MG V to MG VIII, and MG IX to MG X were 15.7 to 15.8, 15.3, 14.7, 13.4 to 13.7, and ≤12 h d −1, respectively. A significant negative linear relationship between the critical photoperiod and relative maturity group (RMG) was found. It is of particular importance for the quantification of soybean photoperiod response and precise prediction of the developmental process. More importantly, the critical photoperiod obtained in this study will help breeders to synchronize the flowering time of parents from distant geographic origins and break the reproductive isolation among different ecotype cultivars.